O contexto de desenvolvimento expert de atletas masculinos de basquetebol da categoria sub-19 anos de Minas Gerais da temporada 2011 - Cleiton Pereira Reis (2012)
During the base category phase of their training, the basketball athletes must have an appropriate structure to become professional players. Therefore, the objective of this study was to analyze whether the context of development of male basketball players U-19 of Minas Gerais is suitable for enabling athletes to become professional. The participants of this study consisted of 47 athletes from five Under-19 teams of Minas Gerais, together with their main coaches and 47 athletes from five Brazilian professional basketball teams. All volunteers are male. The instruments used were: Questionnaire on the Context of Practice for basketball athletes, as applied to athletes; the Inventory of the Basketball Coach Profile and semi-structured interview aimed at coaches of the Under-19 categories of Minas Gerais. For quantitative analysis, we employed the Shapiro-Wilk test to establish the normality of the answers, "t" test or Mann-Whitney test according to normality of the data, and chi-square test for nominal qualitative responses. For qualitative data, the transcript of the interviews were made and, later, a qualitative analysis was conducted, focusing on the content collected, called Meaning Units. The quantitative and qualitative results were presented and discussed together, and classified according to the model of the coach by Côté et al. (1995). Athletes in the Under-19 teams of Minas Gerais, in general, began the practice of basketball in a belated fashion, a situation that did not happen to professional athletes. Basketball Coaches interviewed stressed that the athletes in the state initiate in the sport with little motor experience, which makes the learning process more difficult. These individuals also highlight the dilemmas of the "basketball coach" profession in Minas Gerais, since many lack adequate remuneration and therefore do not devote full time to the office, thus acquiring other jobs. This context, together with the absence of an assistant coach and physical trainer, affect the planning of training. These professionals also point out that the lack of public spaces for basketball practice and the absence of a governmental program that makes the sport more accessible are serious problems that need to be addressed. In addition, to these professionals the educational institutions have little influence on the formation of basketball players, since the physical education classes are precarious and sports in schools and universities are not part of public policies. Professional athletes trained at more structured institutions since sports initiation, and thus had the opportunity to be better prepared physically, technically, tactically and nutritionally, until they turn 19; they also acquired more competitive experience, because the amount of matches played between 16 and 19 years of age was significantly higher. However, when comparing the groups, the athletes spent similar time in hours of training in the base category. It stands out for both groups: the professional of the area of Sports Psychology was not a feature made available by sports institutions; there was a partial involvement of parents in the sporting life of children, since most of them financially supported the start of his career, yet they were often not present at practices and games. The conclusion of this work is that the athletes of the under-19 teams of Minas Gerais, in the 2011 season, are not inserted in the appropriate framework to become professional players.